Bio-inspired creation of heterogeneous reaction vessels via polymerization of supramolecular ion pair - Dong, Ke (Nat Commun, 2019)
Precise control of the outer-sphere environment around the active sites of heterogeneous catalysts to modulate the catalytic outcomes has long been a challenge. Here, we demonstrate how this can be fulfilled by encapsulating catalytic components into supramolecular capsules, used as building blocks for materials synthesis, whereby the microenvironment of each active site is tuned by the assembled wall. Specifically, using a cationic template equipped with a polymerizable functionality, anionic ligands can be encapsulated by ion pair-directed supramolecular assembly, followed by construction into porous frameworks. The hydrophilic ionic wall enables reactions to be achieved in water that usually requires organic solvents and also facilitates the enrichment of the substrate into the hydrophobic pocket, leading to superior catalytic performances as demonstrated by the industrially relevant hydroformylation. Remarkably, the formation of the supramolecular assembly and catalyst encapsulation further engenders reaction selectivity, which reaches an even greater extent after construction of the porous framework.